2018
DOI: 10.1080/07448481.2018.1536058
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between alcohol use and physical activity in US college students: Evidence for directionality

Abstract: OBJECTIVE-To investigate directionality of the association between alcohol use and physical activity in a college student sample, longitudinally across three time points. PARTICIPANTS-396 undergraduate students from a large university in the United States (62% women). METHODS-Self-report data of alcohol use and physical activity were collected at three timepoints with 3-month lags between waves. Random-intercept cross-lagged panel modeling was used to disentangle within-and between-person effects. RESULTS-Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
(62 reference statements)
0
20
1
Order By: Relevance
“…Moreover, Jurak et al suggested that being physically active is a simple and effective way of addressing the adverse effects of COVID-19 [ 42 ]. In contrast to our results, there is strong evidence for the existence of a positive association between alcohol consumption and PA [ 43 , 44 , 45 ]. Additionally, another study reported that moderate drinkers and heavy drinkers were more likely than abstainers to have physically active lifestyles in data representative of the U.S. population [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, Jurak et al suggested that being physically active is a simple and effective way of addressing the adverse effects of COVID-19 [ 42 ]. In contrast to our results, there is strong evidence for the existence of a positive association between alcohol consumption and PA [ 43 , 44 , 45 ]. Additionally, another study reported that moderate drinkers and heavy drinkers were more likely than abstainers to have physically active lifestyles in data representative of the U.S. population [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Many students may have found that their college level drinking habits were not endorsed within their family homes and adjusted accordingly. There are also additional explanations outside of the scope of the current study, such as decrease in peer pressure [ 19 ], change in caloric intake and physical activity [ 20 ], and loss of financial opportunities [ 21 ]. These, and others, should be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…has been described to reduce the association between alcohol consumption and risk of death [ 37 ], whereas others have found an association between higher P.A. and high levels of alcohol consumption [ 38 , 39 ]. Research indicates that college students who engage in regular vigorous physical activity are more likely to participate in social gatherings and show a higher acceptance for alcohol consumption [ 40 ].…”
Section: Discussionmentioning
confidence: 99%